Binarizing photographed document images 2025 quality, time and space assessment - Chaves, Gustavo P., author; Vieira, Thaylor, author; de F. P e Silva, Gabriel, author; Lins, Rafael Dueire, author; Simske, Steven J., author; ACM, publisher (Colorado State University. Libraries, 2025)
Image binarization is fundamental for document image processing. The performance of binarization algorithms depends on several factors that range from the quality of the digitalization devices to the intrinsic features of the document itself and the kind and intensity of the noises present in the image. This assessment on binarizing photographed documents evaluated the quality, time, space, and performance of five new algorithms and ninety-eight "classical" algorithms. The test data set is composed of laser and deskjet printed documents, photographed using six widely used mobile devices with the strobe flash on, off, and in auto modes under three different angles and places of capture.
Keywords: documents; binarization algorithms; quality evaluation; space evaluation; time evaluation